On axial symmetric stress state of uniformly layered space with system of periodical inner disk-shaped cracks - V. N. Hakobyan; L. L. Dashtoyan; Ye. V. Murashkin (National Academy of Sciences of Armenia)
This paper considers the axisymmetric stress state of piecewise homogeneous, uniformly layered space formed by alternate junction of two heterogeneous layers with same thickness, which contains the periodical systems of circle disk-shaped parallel cracks in median plane. The governing system of integral equations for problem is obtained using the Hankel integral transformation. Using rotation operators the governing system of equations is reduced to the system of Fredholm integral equation of second kind. The system is solved by the method of mechanical quadratures. The numerical analysis is carried out and the regulations for changing of intensity factors of fracture stresses and opening of crack depending on physical and mechanical and geometrical characteristics of problem are revealed. В статье рассматривается осесимметричное напряжённое состояние кусочно-однородного, равномерно слоистого пространства, образованного чередующимся соединением двух неоднородных слоев одинаковой толщины, которые содержат периодические системы круглых дискообразных параллельных трещин в срединных плоскостях. Получена система определяющих уравнений задачи в виде системы интегральных уравнений типа Фредгольма, решение которой построено методом механических квадратур. Проведён численный анализ и выявлены закономерности изменения коэффициентов интенсивности разрушающих напряжений и раскрытия трещин в зависимости от физико-механических и геометрических характеристик задачи. Աշխատանքում դիտարկված է հավասար հաստություններ ունեցող երկու անհամասեռ շերտերի հաջորդական միացումից ստացված կտոր առ կտոր համասեռ, շերտավոր տարածության առանցքահամաչափ լարվածային վիճակը, երբ շերտերի միջին հարթության մեջ առկա են զուգահեռ, շրջանաձև ճաքերի պարբերական համակարգեր: Ստացվել է խնդրի որոշիչ հավասարումները Ֆրեդհոլմի տիպի երկու ինտեգրալ հավասարումների համակարգի տեսքով, որի լուծումը կառուցված է մեխանիկական քառակուսացման բանաձևերի մեթոդով: Ուսումնասիրված են քայքայող լարումների ինտենսիվության գործակիցների և ճաքերի բացվածքների փոփոխման օրինաչափությունները՝ կախված ֆիզիկամեխանիկական և երկրաչափական բնութագրիչներից:
Keywords: Physics; Mechanics of deformable solids